IMPLICATIONS OF IMPLEMENTING MEDIATION AS A MEANS OF DIVORCE CASE SETTLEMENT - Zavira Aulia; Mia Mia (Universitas Labuhanbatu, 2024)
Mediation is a humane and fair way of resolving disputes as an alternative to dispute resolution (ADR) because mediation in making decisions through a peace agreement allows the disputing parties to maintain a harmonious and fair relationship. After all, both parties can negotiate a settlement. to solve problems, and the result is a win-win solution. As the organizer of the Supreme Court of the Republic of Indonesia, the Supreme Court has provided several ideas to facilitate the process of resolving disputes in court to obtain the best results. A fairly progressive idea is to optimize mediation institutions in resolving civil cases. Mediation in the Religious Courts is a bridge, a process of conciliation efforts between couples who file for divorce. In divorce mediation, this procedure is carried out by an appointed judge by a religious court.Keywords: Divorce, Effectiveness, Settlement of Divorce Cases Through Mediation